Analisis Hukum terhadap Anak yang Sudah Kawin sebagai Subyek yang Berhadapan dengan Hukum (Studi Kasus Putusan Pengadilan Negeri Sampit Nomor: 03/Pid.Sus Anak/2015/PN.Spt) - Nanang Ibrahim Soleh; Heriamariaty; Thea Farina; Nor Asriadi (Journal of Environment and Management, 2020)
Children are gifts and entrusted from God who are given talents and dignity as a whole creature. During their lifetime, children sometimes face legal problems such as narcotics abuse. This becomes complicated while the child has been married and being a subject against the law. The determination the age limit for children is still a debate because sev-eral laws and regulations provide different figures. This is, indeed, a crucial matter because it will affect legal conse-quence to the children, especially for those who deal with narcotics crime. Based on this point of departure, the authors examine Sampit District Court Decision Number: 03/Pid.SusAnak/2015/PN.Spt regarding narcotics abuse by a married child.